Magnetic Quasi-Phase Matching All-Fiber Isolator. (13th April 2010) - Lu, Chunte A.; Moore, Gerald T.
Abstract : We have experimentally demonstrated an all-fiber optical isolator with 20 dB isolation. The result shows that the quasi-phase matching technique via a meter-long magnet array is highly feasible to generate more than 45 degrees of Faraday rotation in the fibers. The all-fiber isolator can also be temperature tuned to operate between 1048 nm and 1066 nm wavelength.